Egalitarianisme Pendidikan Islam: (Telaah atas Pemikiran M. Fethullah GÅ±len dan Korelasinya dengan Pendidikan Islam di Indonesia) - Mohammad Thoha (Bidayatuna, 2022)
M. Fethullah Gülen, with its Gűlen Movement, pioneers the movement of social humanity. The primary mission is the implementation of values: love, tolerance, humanity, togetherness; sincerity; education, parenting, freedom, democracy, art, and environmental conservation. In this movement, education becomes an urgent mission to build humanity's values. In Indonesia, those values are described in a powerful bond of character education. Islamic boarding school (pesantren), the oldest Islamic studies, has proved to have outcomes of education that contain humanity values. Panca Jiwa of pesantren, which consists of honesty, simplicity, high morality, breadth of knowledge, and experience training, is the evidence of the pesantren education system that focuses on egalitarianism and the same value of humanism. This short article tries to look for the successful key of the education model of the Gűlen Movement and correlates with the Islamic education system in Indonesia